Arp1, an actin-related protein, in Plasmodium berghei - Siden-Kiamos, Inga; Schüler, Herwig; Liakopoulos, Dimitris; Louis, Christos (Molecular and biochemical parasitology, 2010)
Actin-related proteins (Arps) constitute a family of eukaryotic cytoskeletal proteins involved in such diverse events as cell motility, cytokinesis, vesicle transport, and chromatin remodelling. Previously, in a study of Plasmodium berghei gene expression in ookinetes and oocysts, we detected stage-specific increased expression of a gene encoding an Arp. Here we further characterize this gene and the encoded protein. We present a phylogenetic and three-dimensional modelling analysis as well as cell biological and genetic data that support classification of this gene as being an orthologue of the actin-related protein 1 (Arp1). This gene was found to be expressed in asexual stages as well as in the mosquito stages of the parasite, both on the transcript and protein level. Our attempts to delete the gene in the parasite for functional studies were unsuccessful, suggesting that it may be essential. The protein was localized apically of the nucleus in ookinetes, and in combination with the known function of Arp1 proteins, this suggests a role in vesicular transport. Expression of the gene in Saccharomyces cerevisiae resulted in toxic effects and interference with the yeast cytoskeleton.